"Parental Role and Participation in Children's Education: A Reconstruction from the Islamic Educational Perspective" - Suyono (Al-Hikmah: International Journal of Islamic Studies, 2025)
This study aims to reconstruct the role and participation of parents in children's education from the perspective of Islamic education through a literature review approach. The research draws upon a range of primary and secondary sources, including the Qur’an, Hadith, and contemporary scholarly works in the field of Islamic education. The findings indicate that, within Islam, parents are regarded as the primary murabbi (educators), entrusted with instilling the values of tawhid, noble character (akhlaq), and essential life skills from an early age. Parental participation is understood not only in terms of material support but also through emotional, spiritual, and intellectual involvement in the educational process, both at home and in collaboration with formal educational institutions. This reconstruction highlights the importance of effective communication, exemplary behaviour, and the consistent practice of Islamic values in daily life. The study recommends a model of parental involvement grounded in tarbiyah Islamiyah, which is contextually relevant to the challenges of the modern era and capable of nurturing a generation that is knowledgeable, ethical, and positively engaged in society.